2008
DOI: 10.1099/jmm.0.2008/000588-0
|View full text |Cite
|
Sign up to set email alerts
|

Daptomycin non-susceptible meticillin-resistant Staphylococcus aureus USA 300 isolate

Abstract: Daptomycin is a novel bactericidal agent active against Gram-positive pathogens including meticillin-resistant Staphylococcus aureus (MRSA). Our case is unique in the description of an MRSA USA 300 isolate that developed decreased susceptibility to daptomycin during daptomycin and vancomycin therapy. Directed sequencing detected a previously reported mutation in mprF, resulting in a T345A substitution, associated with non-susceptibility to daptomycin. Case reportA 40-year-old white male with a previous history… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 17 publications
2
83
0
Order By: Relevance
“…Several studies identified SNPs in the mprF gene of S. aureus clinical isolates, or laboratory strains evolved in vitro under antibiotic pressure. 72-83 Genome analysis revealed additional SNPs in genes such as rpoB (a polymerase subunit), capB (for capsular polysaccharide synthesis), and the promoter region of the dltABCD operon which is known to increase CAMP resistance (Fig. 2).…”
Section: Single Nucleotide Polymorphisms: Gain Of Function Mutations mentioning
confidence: 99%
“…Several studies identified SNPs in the mprF gene of S. aureus clinical isolates, or laboratory strains evolved in vitro under antibiotic pressure. 72-83 Genome analysis revealed additional SNPs in genes such as rpoB (a polymerase subunit), capB (for capsular polysaccharide synthesis), and the promoter region of the dltABCD operon which is known to increase CAMP resistance (Fig. 2).…”
Section: Single Nucleotide Polymorphisms: Gain Of Function Mutations mentioning
confidence: 99%
“…Mutations in mprF, typically in the form of single-nucleotide polymorphisms, have been identified in most daptomycin-NS S. aureus strains investigated to date (88)(89)(90)(95)(96)(97)(98). In one study of a laboratory-derived daptomycin-NS S. aureus strain, mutation to mprF was shown, by array-based DNA hybridization and comparison, to consistently be the first genetic adaptation accompanying a daptomycin MIC of Ͼ1 g/ml (96).…”
Section: Daptomycin Nonsusceptibility In Staphylococcus Aureusmentioning
confidence: 99%
“…A number of case reports have documented the emergence of daptomycin-NS S. aureus isolates during unsuccessful therapy with this agent (see Table S1 in the supplemental material) (76,(85)(86)(87)(88)(89)(90). In most instances, NS isolates emerged in the setting of recalcitrant, deep-seated infections and those associated with a high burden of the infecting organism, such as endocarditis, catheter-related bacteremia, or an undrained abscess (Table 2) (91).…”
Section: Daptomycin Nonsusceptibility In Staphylococcus Aureusmentioning
confidence: 99%
“…This might be especially true for MRSA pneumonia, due to suboptimal penetration of vancomycin in the alveolar lining fluid [17]. Resistance to the newest antibiotics licensed to treat MRSA infections, linezolid and daptomycin has already emerged [18][19][20][21], although it is confined to a few cases. Therefore, the problem is two-fold: the therapeutic options to treat MRSA infections are limited and, in addition, MRSA also tends to acquire resistance to the newest antibiotics.…”
Section: Mrsa Highlightsmentioning
confidence: 99%